Evaluation of the Effectiveness of Internal Control for Improving the Quality of Public Services at the Pangkalan Susu Port Authority Office - Khairani Yahya; Irawan Irawan (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the effectiveness of the implementation of the Government Internal Control System (SPIP) in improving the quality of public services at the Class IV Pangkalan Susu Harbormaster and Port Authority Office (KSOP). The background of this research is based on the importance of good governance to ensure transparent, accountable, and responsive public services to public needs. The SPIP, as stipulated in Government Regulation Number 60 of 2008, is a crucial instrument in boosting government apparatus performance through five main elements: the control environment, risk assessment, control activities, information and communication, and monitoring. This study used a descriptive qualitative approach, collecting data through in-depth interviews, field observations, and documentation studies. The research subjects consisted of structural officials and implementing staff at the Class IV Pangkalan Susu KSOP. Data were analyzed using reference to the five SPIP elements to identify strengths, weaknesses, opportunities, and challenges in its implementation. The results indicate that all SPIP elements have been implemented consistently and effectively. A conducive control environment is reflected in the leadership's commitment to integrity and work ethics. Risk assessments are conducted systematically to mitigate potential obstacles to service delivery. Control activities are carried out according to standard operating procedures, supported by service digitization, which simplifies administrative processes and speeds up service times. Information and communication are transparent through various media, while monitoring is carried out continuously to ensure service quality is maintained. These findings reinforce the relevance of stewardship theory, where public officials act as public servants oriented toward the public interest, integrity, and responsibility. The implications of this research emphasize the need to strengthen digital innovation, improve human resource competencies, and conduct regular evaluations to ensure the continued effectiveness of the SPIP in supporting excellent public services.